2010
DOI: 10.1007/s10815-010-9419-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of short-term preconceptional exposure to particulate air pollution on treatment outcome in couples undergoing in vitro fertilization and embryo transfer (IVF/ET)

Abstract: Purpose To assess the potential effects of short-term exposure to particulate air pollution during follicular phase on clinical, laboratory, and pregnancy outcomes of women undergoing IVF/ET. Methods Retrospective cohort study of 400 first IVF/ET cycles of women exposed to ambient particulate matter during follicular phase. Particulate matter (PM) was categorized into quartiles (Q 1 : ≤30.48 µg/m 3 , Q 2 : 30.49-42.00 µg/m 3 , Q 3 : 42.01-56.72 µg/m 3 , and Q 4 : >56.72 µg/m 3 ). Results Clinical, laboratory, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 37 publications
2
47
0
Order By: Relevance
“…Preimplantation hypothesis proposes that in some circumstances there are more favourable development or survival of X or Y bearing sperm or survival of male or female embryos 23–25. In a previous study of our group we have shown that exposure to PM during the preconception period are associated to early pregnancy loss in women undergoing in vitro fertilisation26 and thus there is also another possibility to explain the changes in sex ratio by sex specific increases in intrauterine death or stillbirth.…”
Section: Discussionmentioning
confidence: 88%
“…Preimplantation hypothesis proposes that in some circumstances there are more favourable development or survival of X or Y bearing sperm or survival of male or female embryos 23–25. In a previous study of our group we have shown that exposure to PM during the preconception period are associated to early pregnancy loss in women undergoing in vitro fertilisation26 and thus there is also another possibility to explain the changes in sex ratio by sex specific increases in intrauterine death or stillbirth.…”
Section: Discussionmentioning
confidence: 88%
“…), or on the rates of embryo implantation and pregnancy. On the other hand, they found a statistically significant increase of 5% in the risk of early pregnancy loss per unit increase in follicular phase PM10 exposure, leading to an increased rate of early miscarriages among women exposed to the highest quartile of concentrations of PM10 [35]. In another study on 531 pregnant women, the same authors found that women exposed to high concentrations of large particulate matter (PM10) during the follicular phase of the ovarian cycle had a two-fold increased rate of early miscarriages, no matter if the conception was natural or the result of IVF [36].…”
Section: Resultsmentioning
confidence: 97%
“…Altogether, the data from the 3 available human studies about air quality and IVF results provide a weak level of evidence because they consist in retrospective studies, with long observation periods (7 [34] to 10 years [35,36] during which effectiveness of IVF procedures may have improved), with approximated exposures based either on estimated levels from national models of air quality [34] or on average daily exposure of an entire city [35,36], without accounting for the exact home address [35,36] or its distance from the nearest monitoring station [34] or with residual confounding from tobacco exposure [34]. Furthermore, the results of these studies are discordant regarding PM10, the only air pollutant commonly evaluated by these studies.…”
Section: Resultsmentioning
confidence: 99%
“…Couple-based fecundability was assessed in Teplice, where pregnancy in the first month of unprotected intercourse was less likely when couples were exposed to higher levels of nitrogen dioxide (NO 2 ) and PM 2.5 (9). NO 2 was associated with lower live birth rates and PM 2.5 with decreased conception rates after in vitro fertilization (IVF),(10) whereas miscarriage rates appeared higher in couples exposed to the highest quartile of PM exposure prior to IVF or embryo transfer(11). In mice, traffic-related pollutant exposures decreased fertility with effects demonstrated for both males and females as well as mating pairs(12;13) and reductions in placental and fetal weight were observed among mice housed near roadways in Brazil(14).…”
Section: 0 Introductionmentioning
confidence: 99%